2020
DOI: 10.1126/sciadv.abb6987
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous robotic nanofabrication with reinforcement learning

Abstract: The ability to handle single molecules as effectively as macroscopic building blocks would enable the construction of complex supramolecular structures inaccessible to self-assembly. The fundamental challenges obstructing this goal are the uncontrolled variability and poor observability of atomic-scale conformations. Here, we present a strategy to work around both obstacles and demonstrate autonomous robotic nanofabrication by manipulating single molecules. Our approach uses reinforcement learning (RL), which … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 32 publications
0
50
0
Order By: Relevance
“…More and more research efforts start to combine data-driven learning algorithms with rigorous scientific or engineering theory to yield novel insights and applications. 9 , 15 , 351 …”
Section: Machine Learning Tutorial and Intersections With Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…More and more research efforts start to combine data-driven learning algorithms with rigorous scientific or engineering theory to yield novel insights and applications. 9 , 15 , 351 …”
Section: Machine Learning Tutorial and Intersections With Chemistrymentioning
confidence: 99%
“… 383 For chemistry applications, RL techniques are being increasingly used for finding molecules with desired properties in large chemical spaces. 9 …”
Section: Machine Learning Tutorial and Intersections With Chemistrymentioning
confidence: 99%
“…Recent studies have already shown the potential of RL in SPM automation. 24,25 The availability of error signals in SPM e.g., the deviation of the signal on which feedback is performed with respect to the operation set point, should further facilitate their implementation. For instance, following an approach where the actions would be the variation of the scanning parameters and the reward the minimization of the error signal.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the adoption of ML methods into materials analysis has seen rapid recent growth [28][29][30] and this has been followed by an equivalent growth in its applications to image analysis in SPM [31][32][33][34][35][36]. Here we build upon our ML method for predicting molecular structure from AFM images [37], to predict the electrostatic field of the sample molecule.…”
Section: Methodsmentioning
confidence: 99%